Application of mold-bag sleeve valve pipe grouting technology for karst reinforcement during shield tunneling - Li, Taifeng; Feng, Xin; Li, Jiehua; Qu, Linjun; Ji, Fuquan (Frontiers in Earth Science, 2025)
When traversing strata characterized by highly developed karst formations, shield tunneling machines are susceptible to incidents such as head sinking, surface collapse, and water inrushes. Consequently, karst reinforcement becomes a critical factor in ensuring the safety and success of shield tunneling operations in such geological conditions. However, conventional grouting technologies often face challenges, including severe grout leakage and suboptimal reinforcement outcomes, thereby introducing significant risks to tunneling activities. In this study, the limitations of traditional sleeve-valve pipe grouting technologies in reinforcing karst strata were examined, using the Dapeng Branch Line project of the Shenzhen-Huizhou Intercity Railway as a case study. To address these issues, a mold-bag sleeve-valve pipe grouting technology, specifically designed for karst reinforcement, was developed. Its construction procedures and key technical aspects were systematically investigated, and a field grouting test was performed to assess the applicability and reliability of the proposed method. The results indicated that, in karst strata with extensively developed fissures, conventional sleeve-valve pipe grouting methods encountered significant problems, including grout leakage, grout surfacing, and the inability to retrieve intact reinforced bodies from karst cavities. Consequently, the karst treatment effect failed to meet the requirements. In contrast, the proposed mold-bag grouting technology enables precise grouting in karst cave areas, reducing grout loss and forming complete reinforced bodies within the karst cave areas.